FRUIT MORPHOLOGY AND PHYSICAL AND PHYSIOLOGICAL QUALITY OF SEEDS OF JILOEIRO CULTIVARS - Martins, A. R.; Paraíso, H. A.; Gomes, L. S. P.; Costa, C. A.; Brandão Júnior, D. S.; dos Santos, J. C. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The objective of the work was to determine the morphological aspects of fruits and the physical and physiological quality of the seed of cultivars of jiloeiro (Solanum gilo Raddi). The experiment was carried out at the Laboratory of Production Analysis of the Institute of Agricultural Sciences of the Federal University of Minas Gerais (LAS - ICA / UFMG). As cultivars were the Gigante Jaíba, the Compridogrande river, the Round Morro and the Long Green. Determination of moisture content, fresh and dry mass of fruits and seeds, germination, emergence, normal seedling counting, germination and emergence rate index. The experimental design was completely randomized with four replicates. The results were submitted to analysis of variance, thus adopting the 5% probability test. A cultivar Gigante Jaíba stood out for presenting the results of fresh dry mass and mass of one thousand seeds. The testes of germination and vigor were possible as cultivars of cultivars at different levels of physiological quality, standing out as cultivars Gigante Jaíba and Comprido Grande Rio.